Alternative cryoprotectans suitable for a slow freezing method of epididymal spermatozoa of alpaca (Vicugna pacos) - Canorio Pariona, Nadia (2015)
The objective of this study was to use alternative cryoprotectans suitable for freezing epididymal spermatozoa of alpaca (Vicugna pacos) in a slow freezing method. Epididymides obtained in the slaughterhouse of Huancavelica city were transported at 4 °C in saline solution to the laboratory in Lima, Peru. The sperm cells were extracted from the epididymis and incubated in HAMF10 medium. The Tes-Tris-Yolk-Citrate medium was used and supplemented with the cryoprotectants dimethyl sulfoxide (Me2SO4) at 0.5, 0.25 and 0.125M concentrations, and dimethylacetamide (DMA) at 0.75, 0.385 and 0.18M concentrations, and compared with a control group cryopreserved with glycerol 0.6M. Motility, viability and integrity of membrane before and after freezing were assessed. The results showed a better viability and membrane integrity post-freezing when using DMA 0.375M (p<0.05). Motility was better with Me2SO4 0.25 and 05M and DMA 0.375 and 0.75M (p<0.05).